Case report of atypical Still's disease: a diagnosis of exclusion - Yerra, Sandeep; Tlhabano, Letlhogonolo; Vasamsetty, Tejaswini (My University, 2016)
Introduction: We present an unusual presentation of a 39-year-old man with myalgias and shortness of breath. Chief complaints: The patient presented to the emergency department with complaints of myalgias, shortness of breath and palpitations. During this hospitalization, he had multiple episodes of tachycardia and desaturation. The patient had elevated troponins and creatinine kinase. Differential diagnosis included pericarditis, pneumonia and malignancy. Investigations: The patient had elevated ferritin and erythrocyte sedimentation rate. Outcome: The patient had adult Still’s disease. Lesson: This case shows how the presentation and symptom complex of Still’s disease together with the lack of specific serological markers can misguide the diagnosis.